2020
DOI: 10.3390/su12104297
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Sustainability Reporting and Financial Performance

Abstract: In the past few decades, business performance has been approached from a multidimensional perspective, because a pro-active corporate sustainability reporting system for assessing the financial performance of an organization should at least address impacts at the organization and community levels, as well as the resulting associated social impacts. The purpose of this research was to identify the accessibility of corporate sustainability reporting instruments for Romanian managers and their role in increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 82 publications
0
26
0
8
Order By: Relevance
“…However, they obtained very weak evidence for a significant relationship between governance and economic performance, with only one significant effect in 2015. According to Oncioiu et al [57] indicators of CSR can be incorporated into companies' financial reports and can convert sustainability measures into a real value for all parties.…”
Section: Background On Non-financial Disclosure and Hypothesis Developmentmentioning
confidence: 99%
“…However, they obtained very weak evidence for a significant relationship between governance and economic performance, with only one significant effect in 2015. According to Oncioiu et al [57] indicators of CSR can be incorporated into companies' financial reports and can convert sustainability measures into a real value for all parties.…”
Section: Background On Non-financial Disclosure and Hypothesis Developmentmentioning
confidence: 99%
“…Oncioiu et al [ 20 ] showed that, in Romania, the circular economy is seen as a strategy for the company, the circular economy activities of SMEs being at the beginning. The study results showed that after 2010 more than half of the analyzed companies were engaged in activities specific to the circular economy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reporting on social responsibility activities should address the impacts at the organization and community level, as well as the results of the associated social impacts for assessing the financial performance of an organization [ 20 ]. Popescu and Popescu [ 39 ] found that Romanian entities are aware of the importance and advantages of corporate social responsibility correlated with increasing profit, performance and productivity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…El índice ESG empleado en este estudio se correlaciona de manera positiva con la rentabilidad de las empresas, estimada a través de la ratio rOA y rOE. Este hallazgo, se suma a la amplia lista de investigaciones en el campo de las finanzas que han corroborado esta relación positiva tanto a nivel de mercados desarrollados como emergentes (Laskar et al, 2017;Oncioiu et al, 2020;Lassala et al, 2017).…”
Section: Conclusionesunclassified
“…A nivel internacional, en los últimos años, existen varias investigaciones que examinan la relación entre las prácticas de sostenibilidad empresarial y el desempeño corporativo a largo plazo a partir del estudio de empresas que cotizan en los mercados financieros. Al respecto, autores como Ameer y Othman (2012); Laskar, Chakraborty y maji (2017); Lassala, Apetrei y Sapena (2017); Weber (2017); Nizam, ng, Dewandaru, nagayev y nkoba (2019); Pérez et al (2020) y Oncioiu et al (2020) abordan las prácticas corporativas de sostenibilidad, los informes corporativos de sostenibilidad y su papel en el aumento del performance financiero de las organizaciones.…”
Section: Introductionunclassified